2005
DOI: 10.1177/152692480501500406
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplant Recipients' First Year of Posttransplant Recovery: A Longitudinal Study

Abstract: A longitudinal study of 20 liver transplant recipients was conducted to investigate their posttransplant recovery experience. Data were collected using semistructured interviews at 6 weeks, 6 months, and 1 year after transplantation. Qualitative analysis of data revealed physical, psychological, social, economic, and spiritual dimensions of recovery. Findings reflect ongoing improvement of physical health and functionality for most recipients. Those with continuing health problems often suffered from preexisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 40 publications
(65 reference statements)
0
17
0
Order By: Relevance
“…500 recipients have since recieved a kidney by this donation method (NHSBT 2016 [1] ). Directed altruistic donation was made possible in the UK in 2013 (HTA 2012 [2] ). As this enables donation to a specified individual not previously known to the donor, it was anticipated that this was likely to occur as a result of social media campaigns.…”
Section: Methods: We Retrospectively Reviewed All Ltx Performed In Vamentioning
confidence: 99%
See 2 more Smart Citations
“…500 recipients have since recieved a kidney by this donation method (NHSBT 2016 [1] ). Directed altruistic donation was made possible in the UK in 2013 (HTA 2012 [2] ). As this enables donation to a specified individual not previously known to the donor, it was anticipated that this was likely to occur as a result of social media campaigns.…”
Section: Methods: We Retrospectively Reviewed All Ltx Performed In Vamentioning
confidence: 99%
“…This prevalence is high compared to the UK paediatric prevalence of 1.1%. [2] The 3 patients successfully transplanted were 7, 9 and 17 years at time of transplant, 2 out of 3 were pre-emptively transplanted with a live related donor. Their ASD severity ranged from non-verbal to high functioning autism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transplantation offers recipients prolonged life spans and the potential for restored independence and productivity (Gorevski et al 2011, van der Mei et al 2011, Huda et al 2012). Patient's participation in the workforce and in leisure activities is a key aspect of their functional recovery (Jones 2005, van der Mei et al 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…31 It has also been noted that liver transplant patients need psychological and social support from both their families and health professionals. 32 In addition, Keidar and associates (2001a) 18 reported that support group interventions had a positive influence on relationships between the family members of liver, kidney, and pancreas transplant patients. Van Ginneken and associates (2011) 16 showed that exercise and diet improved patients' autonomy, roles in their families, and social relationships.…”
Section: Effects Of the Support Group Intervention On Psychological Amentioning
confidence: 99%